The Effectiveness of Health Education in Reducing Anxiety Levels in Primigravida Trimester III - Fatimatuz Zahro; Iis Hanifah; Sri Wahyuningsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The study purpose was Anxiety in primigravida pregnant women in the third trimester is a common condition and can interfere with psychological readiness in caring for newborns. This study aims to analyze the influence of health education on the level of primigravida anxiety in the third trimester at the Panasea Inpatient Main Clinic. Materials and methods. The study used a quasi-experimental design with a one-group pretest–posttest design and included 40 respondents selected through accidental sampling. Interventions were carried out through structured counseling on newborn care. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HAM-A) instrument. Results. Wilcoxon test analysis showed p = 0.000 (α < 0.05), indicating a significant decrease in anxiety levels after health education. Before the intervention, the majority of respondents experienced moderate to severe anxiety, while after the intervention, most showed a decrease to mild anxiety levels. These findings show that health education is effective as a promotive and preventive intervention to reduce maternal anxiety and increase readiness to face the role of parent. Conclusions. This research supports integrating health education into routine antenatal programs to improve maternal health.